2009
DOI: 10.1038/sj.bjc.6605110
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in cancer patients in South East England from 1996 to 2005: a population-based study

Abstract: BACKGROUND: Studies from around the world have shown that suicide risk is increased in cancer patients, but no previous detailed analysis has been carried out in England. METHODS: We calculated standardised mortality ratios (SMRs) for suicide in 206 129 men and 211 443 women diagnosed with cancer in South East England between 1996 and 2005, relative to suicide rates in the general population. RESULTS: We found a significantly increased risk of suicide in men (SMR 1.45, 95% confidence interval (CI) 1.20 -1.73) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 31 publications
(75 reference statements)
8
63
2
2
Order By: Relevance
“…An increased incidence of suicide in cancer patients compared with the general public has been demonstrated by several studies [8][9][10][11][12]14,15,17 . Specific tumour sites associated with the highest risk of suicide include lung 22 , stomach 17 and oral cavity 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased incidence of suicide in cancer patients compared with the general public has been demonstrated by several studies [8][9][10][11][12]14,15,17 . Specific tumour sites associated with the highest risk of suicide include lung 22 , stomach 17 and oral cavity 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, mostly from Europe, have demonstrated an increased incidence of suicide among cancer patients [8][9][10][11][12][13][14][15][16][17] . In one large U.S. study, Misono et al 17 demonstrated that the incidence of suicide was nearly doubled in cancer patients compared with the general population, with variation by the anatomic cancer site.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto ao risco de suicídio, alguns fatores aqui encontrados, como intensidade da dor, uso de psicofármacos ao longo da vida e depressão, são compatíveis com achados de outros trabalhos 5,8,17,18,27 . Não foram encontrados níveis superiores de risco de suicídio no sexo masculino e entre indivíduos divorciados/separados, diferentemente de outros estudos [15][16][17] . Este estudo apontou maior prevalência de depressão em pacientes com câncer do que em pacientes acometidos por outras doenças.…”
Section: Discussionunclassified
“…Em mulheres não houve significância estatística. Em ambos os sexos houve diminuição do risco relativo de suicídio com o aumento do tempo de diagnóstico 16 . Alguns fatores têm sido associados ao comportamento suicida em pacientes com câncer, tais como: sexo masculino, presença de depressão maior, doença maligna com pior prognóstico, declínio da função física, dor, delírio, fadiga, exaustão, falta de esperança, sensação de desamparo e deficiente apoio social 8,[17][18][19] .…”
Section: Introductionunclassified
“…Several studies have reported that suicide risk is the highest during the first year after cancer diagnosis and that risk decreases with time (8). In cancer patients, depression and hopelessness have been identified to be major triggers for suicidal ideas (9,10).…”
Section: Introductionmentioning
confidence: 99%